2018
DOI: 10.1038/s41372-018-0095-x
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of patient monitoring alarms in the neonatal intensive care unit

Abstract: Objective To characterize the rate of monitoring alarms by alarm priority, signal type and developmental age in a Level-IIIB Neonatal Intensive Care Unit (NICU) population. Study Design Retrospective analysis of 2 294 687 alarm messages from Philips monitors in a convenience sample of 917 NICU patients, covering 12 001 patient-days. We stratified alarm rates by alarm priority, signal type, postmenstrual age (PMA), and birth weight (BW) and reviewed and adjudicated over 21 000 critical alarms. Results Of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Device alarms are consistently found to be a source of excessive noise in NICUs, [20,21,26]. Patient monitor alarms are an especially frequent contributor to the noise in NICUs, with an average of 177 alarms/patient/day [27].…”
Section: Discussionmentioning
confidence: 99%
“…Device alarms are consistently found to be a source of excessive noise in NICUs, [20,21,26]. Patient monitor alarms are an especially frequent contributor to the noise in NICUs, with an average of 177 alarms/patient/day [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper investigating the signal type of alarms in the NICU, reported that over 60% of alarms were related to oxygenation monitoring; thus, these represent the major burden of all alarms in newborns population [ 24 ]. In this survey, the setting of the maximum value is influenced by the presence or absence of both written operational procedures and staff training, with attention to hyperoxia conditions.…”
Section: Discussionmentioning
confidence: 99%
“… Protocols for application, positioning and replacement of electrodes and sensors and protocol for the patients' admission and discharge from system were standardised. Delay time for saturation‐related alarms was increased from 10 to 20 seconds based on the findings from 7,23,24 . Averaging time was decreased from 10 to 4 seconds as suggested in 21,25 . An additional red ‘smart alarm’ was introduced to indicate yellow alarms lasting for more than 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…7,23,24 Averaging time was decreased from 10 to 4 seconds as suggested in. 21,25 An additional red 'smart alarm' was introduced to indicate yellow alarms lasting for more than 5 minutes. All modification to alarms are summarised in Table 2.…”
Section: Workflow Optimisationmentioning
confidence: 99%